Repression and Repertoires - Morris, Stephen; Shadmehr, Mehdi (American Economic Review: Insights, 2024)
We formalize Tilly's concept of repertoires of collective action and analyze how state repression affects the variety of observed contentious actions. When repression accelerates with higher levels of antiregime actions (convex repression structure), opposition leaders tend to call for many different forms of contentious actions, thereby generating a wider repertoire. In contrast, when repression decelerates with higher contentious actions (concave repression structure, including indiscriminate repression), opposition leaders tend to call for just one form of contentious action, thereby generating a narrower repertoire. Methodologically, we deliver an analysis for settings in which coordination and delegation are intertwined.
Keywords: Alliances; Conflict Resolution; Mechanism Design; Rent-Seeking; Revolutions, Asymmetric and Private Information; Political Processes